2008
DOI: 10.1089/apc.2008.0040
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Quality of Life Domains of Persons Living with HIV/AIDS in South India in the Era Prior to Greater Access to Antiretroviral Therapy

Abstract: This study sought to examine gender-based differences in the quality of life of men and women living with HIV in South India in the era prior to greater access to antiretroviral therapy. The participants in this prospective longitudinal study consisted of 215 men and 141 women who were administered a quality of life (QOL) instrument comprising five scales: physical well-being, psychosocial well-being, sexual well-being, satisfaction with health care, and strength of partner relationship. Interviews were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
6
11
1
4
Order By: Relevance
“…These findings are coherent with other studies from developing and developed countries [7][8][9][10][11][12][13]15]. Gender differences emerged significantly on Psychological and Spirituality domains.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are coherent with other studies from developing and developed countries [7][8][9][10][11][12][13]15]. Gender differences emerged significantly on Psychological and Spirituality domains.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, women reported poorer QoL than men [7][8][9][10][11][12][13][14][15]. More recently, two studies reported lower scores among men [16,17], and a multi-site study reported similar QoL scores among men and women, with the exception of physical QoL, in which women showed significantly higher scores [18].…”
Section: Gender Age and Quality Of Lifementioning
confidence: 99%
“…[7][8][9][10][11] Past studies have found that females report symptoms more often than males and rely more on feelings of discomfort during physical activity in reporting health related quality of life (HRQL) as compared with males as seen in our study also. 9 According to a WHO report the gender situation in most societies negatively affects women's power and independence.…”
Section: Discussionsupporting
confidence: 64%
“…Entre los dominios de calidad de vida, espiritualidad obtuvo el mayor puntaje (65,7), seguido por el físico (64, 7), psicológico (60,6), relaciones sociales (59,5). Menores puntajes fueron alcanzados en los dominios nivel de independencia (58,6) y medio ambiente (54,5). Se evidenció que los factores bajo nivel socioeconómico y educacional estuvieron asociados con diferentes dominios, denotando la relación entre calidad de vida y condiciones de vida.…”
Section: Introductionunclassified
“…Studies evidence that the quality of life of women with HIV/AIDS is compromised when compared to that of men; however, few studies about this thematic have been developed in developing countries, and few studies analyze women (5)(6) .…”
Section: Introductionmentioning
confidence: 99%